Mechanism of Kupffer cells in hepatitis infected by hepatitis B and C virus - Tan, Yi-qing; Zhu, Xi-wen; Lai, Xing; Gong, Jian-ping; Yin, Qing-gang (International Surgery Journal, 2017)
The infection of hepatitis B virus or hepatitis C virus (HBV / HCV) is the most common cause of the chronic liver disease. Kupffer cells (KCs), the largest number of viscera macrophages, are located in the sinusoid of the hepar and play an extremely significant role in hepatic chronic inflammation after HBV / HCV infection. KCs could affect the secretion of cytokines and the interaction among cells via a variety of signalling pathways and they could regulate the inflammatory response and immune activities as well. The activation of KCs could balance inflammation and anti-inflammation, maintaining the stability of internal environment in vivo. Studies of KCs have the significance of the understanding of pathogenic mechanisms and the access to the treatment of HBV/HCV infection. Meanwhile, such studies might help to delay the development of fibrosis, cirrhosis and even carcinoma of liver after HBV / HCV infection.